Integrating citizen participation and science communication: a proposal for the cultural sector in Villa Clara, Cuba - Manso Rodríguez, Ramón Alberto; Abreu Cortes, Alina Francisca (Scripta Mundi, 2026)
Science communication is an essential component for strengthening the links between research, innovation, and society, especially in cultural spheres where dialogue with the public is crucial. In this context, the problem arises from the limited presence of science communication initiatives aimed at non-specialized audiences in the cultural sector of Villa Clara, where dissemination practices are predominantly directed almost exclusively at specialists. Based on this, the objectives of this study are: 1) to identify the current state of science communication in this sector and 2) to propose a system of actions that enhances citizen participation in research processes. The research adopts a descriptive and mixed-methods approach, supported by a questionnaire administered to a probabilistic sample of 60 cultural researchers, in order to analyze motivations, obstacles, and practices related to science communication. The results reveal, on the one hand, a growing interest in bringing research closer to the community and, on the other, a marked deficiency in the planning of communication activities, where institutional limitations, scarce spaces for interaction, and a partial understanding of the researcher’s communicative role persist. Furthermore, social media, workshops, and science fairs are identified as the most valued avenues for enhancing communication. The study confirms the need to move towards a strategic communication model that integrates science, culture, and citizen participation, so that the community becomes an active agent in the generation, understanding, and application of knowledge in Villa Clara.
Keywords: Science and society; Science communication; Citizen participation; Culture; Cuba